Utilization of Diamond Software as a Measuring Tool for Student Scientific Attitude - Azmi Khusnani; Nursina Sya’bania; Adi Jufriansah; Pujianti Bejahida Donuata; Dian Ahdiany (Department of Physics Education, Universitas Mataram, 2022)
Solid-state is a compulsory subject in the Physics Education study program. Therefore, the level of complexity—depth—of the material taught is moderate. However, students are facing some obstacles in understanding crystal structure material that is related to microscopic structures. This research aims to apply diamond software media to crystal structure material, from which students' scientific attitudes can be discovered. The method used in this study is the qualitative description. The research subjects totaled 23 students. The data collection technique was carried out by measuring students' scientific attitudes after using the Diamond software. The results showed that the Diamond software could be used in Solid State Physics course. In contrast, the scientific perspective showed good results, which is indicated by the scientific attitude questionnaire score reaching more than 80% within the high category. Meanwhile, student responses indicate that the acceptance rate of Diamond software as a learning medium in Solid State Physics course is 86.25%, or falls into the high category.